Cover Image, Volume 1, Issue 3. Issue 3 (26th October 2018) - Unknown
Carbon Black Effect on Bimodal Polyethylene Crystallization: In their work presented in article e10014, Amirhosein Sarafpour, Gholamreza Pircheraghi, Reza Rashedi, and Kamal Afzali explored the crystallization behavior of a bimodal polyethylene (PE) resin that was compounded with three different grades of carbon black. The results of their experiments confirmed the importance of carbon black's presence in the formation of PE crystalline structures and highlighted the effects of different molecular weights of carbon black on the microstructure of the PE resin. The cover image shows a scanning electron micrograph of the semi‐circular aggregates of lamellar plates (spherulites). The establishment of these spherulites (or lack thereof) during crystallization can be dependent on the molecular structure and weight distribution. (DOI:10.1002/PCR210014 )